Aging alters signaling properties in the mouse spinal dorsal horn. (May 2019) - Mayhew, JA; Callister, RJ; Walker, FR; Smith, DW; Graham, BA
A well-recognized relationship exists between aging and increased susceptibility to chronic pain conditions, underpinning the view that pain signaling pathways differ in aged individuals. Yet despite the higher prevalence of altered pain states among the elderly, the majority of preclinical work studying mechanisms of aberrant sensory processing are conducted in juvenile or young adult animals. This mismatch is especially true for electrophysiological studies where patch clamp recordings from aged tissue are generally viewed as particularly challenging. In this study, we have undertaken an electrophysiological characterization of spinal dorsal horn neurons in young adult (3–4 months) and aged (28–32 months) mice. We show that patch clamp data can be routinely acquired in spinal cord slices prepared from aged animals and that the excitability properties of aged dorsal horn neurons differ from recordings in tissue prepared from young animals. Specifically, aged dorsal horn neurons more readily exhibit repetitive action potential discharge, indicative of a more excitable phenotype. This observation was accompanied by a decrease in the amplitude and charge of spontaneous excitatory synaptic input to dorsal horn neurons and an increase in the contribution of GABAergic signaling to spontaneous inhibitory synaptic input in aged recordings. While the functional significance of these altered circuit properties remains to be determined, future work should seek to assess whether such features may render the aged dorsal horn more susceptible to aberrant injury or disease-induced signaling and contribute to increased pain in the elderly.